2020
DOI: 10.1098/rsos.191127
|View full text |Cite
|
Sign up to set email alerts
|

The effect of bed roughness uncertainty on tidal stream power estimates for the Pentland Firth

Abstract: Uncertainty affects estimates of the power potential of tidal currents, resulting in large ranges in values reported for sites such as the Pentland Firth, UK. Kreitmair et al. (2019, R. Soc. open sci. 6 , 180941. ( doi:10.1098/rsos.191127 )) have examined the effect of uncertainty in bottom friction on tidal power estimates by considering idealized theoretical models. The present paper considers the role of bottom friction unce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…The effects modeled from very large arrays (1 GW or more) indicate the potential for substantial changes in the marine environment, although most are highly dependent on the device layout, channel geometry, habitat type, and flow patterns [103]. The process of modeling interactions of MRE devices with the ocean creates a level of uncertainty that may propagate through subsequent steps in estimating power outputs and effects [104]. It will also be important in the future to examine other forcing functions, such as climate change, to determine the potential effects of MRE devices on water flow, wave height, and sediment transport [105].…”
Section: Additional Research Needed To Verify and Understand Resultsmentioning
confidence: 99%
“…The effects modeled from very large arrays (1 GW or more) indicate the potential for substantial changes in the marine environment, although most are highly dependent on the device layout, channel geometry, habitat type, and flow patterns [103]. The process of modeling interactions of MRE devices with the ocean creates a level of uncertainty that may propagate through subsequent steps in estimating power outputs and effects [104]. It will also be important in the future to examine other forcing functions, such as climate change, to determine the potential effects of MRE devices on water flow, wave height, and sediment transport [105].…”
Section: Additional Research Needed To Verify and Understand Resultsmentioning
confidence: 99%
“…bed roughness) and sources of data (e.g. bathymetry and boundary conditions) [24,32], predictions were assessed against available observations of tidal range and currents. We assumed here that the existing validations were sufficient to conduct a comparison of numerical predictions in the three tidal stream energy sites.…”
Section: Methodsmentioning
confidence: 99%
“…According to the measurements of [2], increasing turbulence intensity reduces the power and the thrust by over 10% in extreme cases. The turbulent effects have also been studied numerically in [4], where a horizontal axis tidal turbine operating over an irregular bathymetry has been simulated [5]. Those investigations confirmed that bedform-induced turbulence enhances wake deficit recovery.…”
Section: Introductionmentioning
confidence: 94%